2022
DOI: 10.1109/access.2022.3207760
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Communication Link Performance and Charging Speed in Self-Powered Internet of Underwater Things Devices

Abstract: The energy consumption of the Internet of underwater things (IoUT) nodes is a capital aspect that dramatically affects the applicability of wireless optical technologies in several scenarios, such as ocean monitoring or underwater sensor networks. Simultaneous lightwave information and power transfer (SLIPT) is a cost-effective and energy-efficient solution for energy-constrained wireless systems. Nonetheless, the reported battery-charging times for underwater operations are high, which should be improved to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Specifically, in the context of UOWC, in Reference 8, three SLIPT methods (1) time switching (TS), (2) power‐splitting (PS), and (3) a combination of TS‐PS were considered for a point‐to‐point UOWC and performance was analyzed in terms of ergodic capacity and bit error rate (BER). In Reference 9, authors experimentally demonstrated solar cell based UOWC‐SLIPT setup with on‐off keying and variable DC bias.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in the context of UOWC, in Reference 8, three SLIPT methods (1) time switching (TS), (2) power‐splitting (PS), and (3) a combination of TS‐PS were considered for a point‐to‐point UOWC and performance was analyzed in terms of ergodic capacity and bit error rate (BER). In Reference 9, authors experimentally demonstrated solar cell based UOWC‐SLIPT setup with on‐off keying and variable DC bias.…”
Section: Introductionmentioning
confidence: 99%